ZBrush: Tips & Tricks. - Kittleson, Ryan (linkedin.com, 2016)
Learn tips on how to optimize using ZBrush. Ryan Kittleson explains how to use 3D form modes, hot keys, custom layouts, grids, stamp brushes, and more.